More Than Just a Room: A Scoping Review of the Impact of Homesharing for Older Adults. Issue 2 (3rd May 2020) - Martinez, Laura; Mirza, Raza M; Austen, Andrea; Hsieh, Jessica; Klinger, Christopher A; Kuah, Michelle; Liu, Anna; McDonald, Lynn; Mohsin, Rida; Pang, Celeste; Rajewski, Jennifer; Salomons, Tonya; et al.
Abstract: Background and Objectives: "Aging in place" is commonly defined as the ability to remain living safely and independently for as long as possible either in the home or community of one's choosing. Yet, the literature indicates that older adults prefer to remain specifically in their own homes. Homesharing, an innovative exchange-based housing approach, is a means by which older adults can obtain additional income, companionship, and assistance by renting out a room to a home seeker, potentially increasing capacity to remain living independently in their homes. But what is known about their experiences of homesharing? Research Design and Methods: A scoping review was conducted to map and consolidate the literature related to the experience of homeshare participation for adults aged 55 and older published from 1989 to 2018. Fifteen databases were searched, including 3 medical, 5 social science, and 7 gray literature databases. Following abstract and full-text review, 6 sources were retained for study inclusion. Thematic content analysis was used to identify major themes. Results: Within included studies, 4 major themes were identified: (i) benefits of homeshare participation for older adults; (ii) challenges of participating in homeshare for older adults; (iii) intergenerational engagement as social exchange; and (iv) the key role of agency facilitation. Discussion and Implications: Findings were used to derive practice, policy, and research implications. By focusing on older adults and the ways homesharing impacts their lives, we can better determine the viability of homeshare as a means for improving and prolonging experiences of living at home.